An improved extraction method enables the comprehensive analysis of lipids, proteins, metabolites and phytohormones from a single sample of leaf tissue under water‐deficit stress. (5th June 2020) - Salem, Mohamed A.; Yoshida, Takuya; Perez de Souza, Leonardo; Alseekh, Saleh; Bajdzienko, Krzysztof; Fernie, Alisdair R.; Giavalisco, Patrick
Summary: Phytohormones play essential roles in the regulation of growth and development in plants. Plant hormone profiling is therefore essential to understand developmental processes and the adaptation of plants to biotic and/or abiotic stresses. Interestingly, commonly used hormone extraction and profiling methods do not adequately resolve other molecular entities, such as polar metabolites, lipids, starch and proteins, which would be required to comprehensively describe the continuing biological processes at a systematic level. In this article we introduce an updated version of a previously published liquid:liquid metabolite extraction protocol, which not only allows for the profiling of primary and secondary metabolites, lipids, starch and proteins, but also enables the quantitative analysis of the major plant hormone classes, including abscisic acid, auxins, cytokinins, jasmonates and salicylates, from a single sample aliquot. The optimization of the method, which uses the introduction of acidified water, enabling the complete purification of major plant hormones into the organic (methyl‐ tert ‐butyl‐ether) phase, eliminated the need for solid‐phase extraction for sample clean‐up, and therefore reduces both sampling time and cost. As a proof‐of‐concept analysis, Arabidopsis thaliana plants were subjected to water‐deficit stress, which were then profiled for hormonal, metabolic, lipidomic and proteomic changes. Surprisingly, we determined not only previously described molecular changes but also significant changes regarding the breakdown of specific galactolipids, followed by the substantial accumulation of unsaturated fatty‐acid derivatives and diverse jasmonates in the course of adaptation to water‐deficit stress. Significance Statement: We report on an important methodological improvement for the systemic analysis of plant samples, enabling us to obtain maximal information from a single sample aliquot. The improved extraction method enables the comprehensive analysis of lipids, proteins, metabolites and phytohormones from a single sample of water deficit‐stressed leaf tissue. This analysis allowed us not only to confirm the previously reported water deficit‐induced molecular changes but more importantly to uncover novel regulatory interactions during water deficit.